Isolated Femoral Shaft Fracture in Wakeboarding and Review of the Literature - Henrik Constantin Bäcker; Seth Shoap; Gabor Vasarhelyi; Gergely Pánics (Case Reports in Orthopedics)
Introduction. Wakeboarding is an extreme sport that has shown increasing popularity in recent years, with an estimated 2.9 million participants in 2017. Due to this trend, injuries related to this sport are likely to become more common. Isolated femoral shaft are rare; however, they occur much more frequently in youth as a result of high velocity events, such as dashboard-related injuries. Few studies have addressed injuries related to wakeboarding, and of those that have, most have reported on muscle injuries, ligament ruptures, and sprains. Due to the dearth in literature, we want to present two cases of isolated noncontact femoral shaft fractures that resulted from wakeboarding. Case Presentation. Two 28-year-old, otherwise healthy, wakeboarders—patient A, male, and patient B, female—presented to our Department of Orthopaedics and Sports Medicine with isolated femoral shaft fractures. Both were admitted due to wakeboard-related noncontact injuries, where patient A fell while performing a sit-down start during cable wakeboarding and patient B after attempting a wake-jump. Both patients were being pulled by motorboats at roughly 40 km/h. After clinical examination and radiography, left spiral (AO classification: 32-A1.2) (patient A) and right-sided bending, wedge (AO classification 32-B2.2) (patient B) isolated femoral shaft fractures were diagnosed. No concomitant injuries were reported. For treatment, long reamed locked nails were applied, while the patients were under spinal anaesthesia. Physiotherapy was prescribed postoperatively. Patient A returned to wakeboarding 155 days after the surgery, and patient B returned after approximately half a year. Conclusion. This case series shows that even in noncontact sports such as wakeboarding, high-energy forces applied to the femur can cause isolated femoral shaft fractures. Despite multiple reports in various sports of stress fractures of the femur, there are few publications of direct trauma.